2006
DOI: 10.1677/joe.1.06782
|View full text |Cite
|
Sign up to set email alerts
|

Plasma profiles of adrenocorticotropic hormone, cortisol, α-melanocyte-stimulating hormone, and growth hormone in dogs with pituitary-dependent hyperadrenocorticism before and after hypophysectomy

Abstract: The 6-h plasma profiles of adrenocorticotropic hormone (ACTH), cortisol, a-melanocyte-stimulating hormone (a-MSH), and GH were studied in 17 dogs with pituitarydependent hyperadrenocorticism (PDH) before and after hypophysectomy. The aim of the study was to investigate the relation between the hormone profile characteristics and recurrence of PDH after surgery.The hormones were secreted in a pulsatile fashion. The basal plasma cortisol concentration and area under the curve (AUC) for cortisol were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
9
0
3
Order By: Relevance
“…A circadian rhythm has not been convincingly demonstrated, although 1 study reported higher plasma cACTH concentrations in late afternoon than in the morning . Concentrations of cACTH do not differ between healthy dogs and those with PDH, and its measurement is not useful to screen for HAC . Measurement of cACTH is the most accurate stand‐alone biochemical test for differentiating PDH from AT.…”
Section: Differentiating Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…A circadian rhythm has not been convincingly demonstrated, although 1 study reported higher plasma cACTH concentrations in late afternoon than in the morning . Concentrations of cACTH do not differ between healthy dogs and those with PDH, and its measurement is not useful to screen for HAC . Measurement of cACTH is the most accurate stand‐alone biochemical test for differentiating PDH from AT.…”
Section: Differentiating Testsmentioning
confidence: 98%
“…72 Concentrations of cACTH do not differ between healthy dogs and those with PDH, and its measurement is not useful to screen for HAC. 73 Measurement of cACTH is the most accurate stand-alone biochemical test for differentiating PDH from AT.…”
Section: Endogenous Acth Concentrationmentioning
confidence: 99%
“…Plasma concentrations of thyroid-stimulating hormone (TSH) and thyroxine (Kooistra et al, 2000), and GH and insulin-like growth factor-1 (IGF-1) (Fracassi et al, 2007) were decreased (Table 1), indicating hypopituitarism, secondary hypothyroidism and hyposomatotropism. The pituitaryeadrenocortical system was further investigated by measuring plasma concentrations of ACTH and a-melanocyte-stimulating hormone (MSH) by methods described previously (Hanson et al, 2006). The basal plasma concentration of ACTH was elevated and that of a-MSH was within the reference range (Table 1).…”
mentioning
confidence: 99%
“…16,[47][48][49][50] The samples studied here were ob-tained in the course of consultations during the morning and afternoon. The interest of clinicians in a diagnostic technique depends not only on its accuracy, but also on the practicality of the technique.…”
mentioning
confidence: 99%